Temporal variation in abundance and fecundity of the invading copepod Eurytemora americana in Bahía Blanca Estuary during an unusual year - Berasategui, Anabela Anhi (2009)
Temporal change of biotic and environmental variables was corroborated by a Mann–Whitney/Kruskal–Wallis non-parametric tests, with significant differences ( p 0.01) in all variables throughout the study. Abundance population results showed very high values in relation to those recorded in recent years in Bahı ́ a Blanca Estuary. This response could be due to the unusual combination of environmental factors (polar wave with temperatures 6 C and a drought period with high salinities, 32.7–36.6) recorded during the studied winter period. Significant positive correlations between abundance and salinity ( p < 0.01, n = 226), and hatching success ( p < 0.01, n = 25) as well as a significant negative correlation between abundance and chlorophyll a ( p < 0.01, n = 226) were found. Although E. americana shows a k-strategy within its annual pulse, it presented two markedly distinct behaviours depending on temporal environmental variability. From July to early september, when the estuary evidenced high salinity, low temperature and high food availability, E. Americana showed large females, large clutch size and high hatching success. When environmental conditions became unfavorable from September to October, small females, small clutch size and very low hatching success were observed. The latter is associated with diapause egg laying which ensures pop- ulation recruitment. According to our findings the particular combination of low temperatures, high salinities and high available food (i.e. variables which each year modulate its pulse) during 2007 winter– spring, favored the great development of E. americana . This invading species in its opportunistic role has managed to exploit a vacant niche in the estuary, developing two different behaviours within the k-strategy depending on change in environmental conditions.